Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/jctb.5629
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of components in deep eutectic solvents relieve toxicity and improve the performance of steroid biotransformation catalyzed by Arthrobacter simplex

Abstract: BACKGROUND The discovery of deep eutectic solvents (DESs) has introduced a new class of promising green solvents to overcome many drawbacks associated with organic solvents. In this study, the synergistic effects of the components in the form of DESs on bacterial viability, membrane integrity, and retention of metabolic activity as well as the efficiency of Δ1,2‐dehydrogeneration of cortisone acetate (CA) using whole cells of Arthrobacter simplex were investigated. RESULTS The agar disc diffusion method, viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…These studies indicated that a DEScontaining system can result in a remarkable improvement in the reaction efficiency in respect to the substrate solubility and loading and, consequently, improve the productivity of the biocatalytic process. 35,68,69 For example, DESs used as co-solvents enhanced the efficiency of C1,2-dehydrogeneration by improving the solubility of the highly hydrophobic substrate. 35 To be more precise, the solubility of cortisone acetate in Ch:U (1:2 mol mol −1 ) was improved to 0.0436 mg mL −1 , in comparison with solubility in water (0.0215 mg mL −1 ) and ethanol (0.0280 mg mL 1 ).…”
Section: Substrate and Co-substrate Loadingmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies indicated that a DEScontaining system can result in a remarkable improvement in the reaction efficiency in respect to the substrate solubility and loading and, consequently, improve the productivity of the biocatalytic process. 35,68,69 For example, DESs used as co-solvents enhanced the efficiency of C1,2-dehydrogeneration by improving the solubility of the highly hydrophobic substrate. 35 To be more precise, the solubility of cortisone acetate in Ch:U (1:2 mol mol −1 ) was improved to 0.0436 mg mL −1 , in comparison with solubility in water (0.0215 mg mL −1 ) and ethanol (0.0280 mg mL 1 ).…”
Section: Substrate and Co-substrate Loadingmentioning
confidence: 99%
“…35,68,69 For example, DESs used as co-solvents enhanced the efficiency of C1,2-dehydrogeneration by improving the solubility of the highly hydrophobic substrate. 35 To be more precise, the solubility of cortisone acetate in Ch:U (1:2 mol mol −1 ) was improved to 0.0436 mg mL −1 , in comparison with solubility in water (0.0215 mg mL −1 ) and ethanol (0.0280 mg mL 1 ). Xu et al 69 , when studying asymmetric reduction of 3-chloropropiophenone with immobilised Acetobacter sp.…”
Section: Substrate and Co-substrate Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…Viability assays were carried out and the researchers concluded that the cell membrane of A. simplex in the presence of cholinium chloride was less stable compared to its presence with the different HBDs. The group also found out that the ChCl:Ur mixture was a good co-solvent in the steroid dehydrogenation reaction, and that the initial reaction rate for this reaction was higher compared to the ones that were performed in the DES individual components [42].…”
Section: Applications Of Deep Eutectic Solvents To Oxidoreductase-mentioning
confidence: 99%
“…Several examples have been described in which a (NA)DES was applied in the presence of different types of biocatalysts [27][28][29][30], including their use in redox biotransformations [31,32]. Specifically, NADESs have been employed in selective reductions catalyzed by alcohol dehydrogenases [33][34][35], as well as in oxidations using different types of enzymes [36][37][38][39][40]. Yet, until recently, no examples of the application of DESs as cosolvents in reactions catalyzed by flavin-containing oxidases have been reported.…”
Section: Introductionmentioning
confidence: 99%